LEGAL REGULATION OF THE ACTIVITIES OF NON-GOVERNMENTAL NON-PROFIT ORGANIZATIONS (Scientific journal of the Fergana State University, 2024)
This article presents ideas about the role and importance of non-profit organizations in society. Non-governmental non-profit organizations are one of the important links in society. Having carefully mastered it, you can obtain information about non-profit organizations, their organizational and legal foundations, their place in the political system of society, their significance, forms of non-profit organizations and the order of their membership.